Constat scientifique de l’évolution des précipitations et des températures dans la commune de Korsimoro au centre-nord du Burkina Faso - Ibrahim OUEDRAOGO; Mahamadi ZOUNDI; Joachim BONKOUNGOU (Revue Hybrides)
This work is based on meteorological data from the Bogandé synoptic station, which covers the Korsimoro area. It consists of analysing climatic parameters, in particular rainfall and temperature, from 1991 to 2020. The data was modeled using simple linear trends on graphs representing the monthly or annual averages of the various climatic parameters. This revealed an average rainfall of 669 mm/year, with an average of 48 rainy days per year. An annual average temperature of over 28°C with a rising tendency. The annual average evapotranspiration for the area is 181.73mm and is rising, as well as temperatures over the same period. The analysis of these climatic parameters enables us to see how the climate of the area has evolved through the various fluctuations. It is necessary in this sense that it could facilitate decision-making within the framework of the development of agro-pastoral activities in the commune.